2022
DOI: 10.3389/fbuil.2022.861662
|View full text |Cite
|
Sign up to set email alerts
|

Fire Safety Risk Assessment of Workplace Facilities: A Case Study

Abstract: Workplace facilities are organizational capital assets, which entail high risks of fire occurrences. The fire risks increase based on occupants’ behaviors, lack of awareness and poor workspaces safety management. Thus, fire safety risk assessment is vital to raise awareness about workplace fire-safety culture, and to train employees on effective fire response requirements and methods. The literature lacks studies focusing on managing fire safety at the workplace, and limiting occupants dispossessed behaviors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Periodic inspections and maintenance must include devices known as Active Protective Measures, whose equipment includes emergency lighting, fire detection and alarm, fire extinguishers, fire hydrants and sprinklers, among others, all governed by specific standards and technical instructions that establish rules and guidelines for their maintenance and proper use (Negrisolo, 2019;Hassanain, Al-Harogi, and Ibrahim, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Periodic inspections and maintenance must include devices known as Active Protective Measures, whose equipment includes emergency lighting, fire detection and alarm, fire extinguishers, fire hydrants and sprinklers, among others, all governed by specific standards and technical instructions that establish rules and guidelines for their maintenance and proper use (Negrisolo, 2019;Hassanain, Al-Harogi, and Ibrahim, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A focused review of the literature, in the past ten years, on fire risk assessment in the built environment has identified several studies that reported on the assessment of fire safety conditions in various types of buildings. Fire risk assessment were carried out to the provision and keep of fire protection systems in schools (Baldassarra, 2015;Han, 2020;Hassanain et al, 2022a), office workplace (Nimlyat et al, 2017;Li et al, 2018;Hassanain et al 2022b), education facilities (Ebenehi et al, 2017;Salaheldin et al, 2021), residential buildings (Xin and Huang, 2013;Leung and Chow, 2016;Hamida and Hassanain, 2019), student housing facilities (Agyekum et al, 2016;Hassanain et al, 2018) and health care facilities (Ebekozien et al, 2020;Jaafar et al, 2021;Salim et al, 2021). Yet, the literature lacked studies that focus on community centers type of facilities.…”
Section: Historical Incidents and Previous Studiesmentioning
confidence: 99%
“…Furthermore, this research recognizes the limitations of current laws and regulations pertaining to fire safety in buildings. In particular, the existing legal framework primarily emphasizes the facilitation of safe occupant evacuation during emergencies [39]. Therefore, an additional contribution of this study lies in its dedication to understanding occupants' behavior and their impact on ensuring safe and efficient evacuation processes during fire incidents.…”
Section: Summary Of Previous Studiesmentioning
confidence: 99%